A New Security Protocol Using Hybrid Cryptography Algorithms - Bhole, Darshan; Mote, Aditi; Patil, Rachana (International Journal of Computer Sciences and Engineering, 2025)
A Computer Network is an interconnected group of autonomous computing nodes, which use a well-defined, mutually agreed set of rules and conventions known as protocols, interact with one-another meaningfully and allow resource sharing preferably in a predictable and controllable manner. Communication has a major impact on today’s business. It is desired to communicate data with high security. Security Attacks compromises the security and hence various Symmetric and Asymmetric cryptographic algorithms have been proposed to achieve the security services such as Authentication, Confidentiality, Integrity, Non-Repudiation and Availability.At present, various types of cryptographic algorithms provide high security to information on controlled networks. These algorithms are required to provide data security and users authenticity.To improve the strength of these security algorithms, a new security protocol for online transaction can be designed using combination of both symmetric and asymmetric cryptographic techniques. This protocol provides three cryptographic primitives such as integrity, confidentiality and authentication. These three primitives can be achieved with the help of Advance Encryption Standard,Elliptic Curve Cryptography,XOR-Dual RSA algorithm and Message Digest MD5. It uses Elliptic Curve Cryptography and Advance Encryption both for encryption,XOR-Dual RSA algorithm for authentication and MD-5 for integrity. This new security protocol has been designed for better security with integrity using a combination of both symmetric and asymmetric cryptographic techniques.